An insight into gut microbiota and metabolites in the mice with adenomyosis - Chen, Peipei; Wang, Kun; Zhuang, Mingyan; Fu, Xianyun; Liu, Shidan; Chen, Minmin; Lei, Ya (Frontiers in Cellular and Infection Microbiology, 2023)
Background Adenomyosis (AM) is a benign uterine disease characterized pathologically by the invasion of endometrial tissue into the myometrium. The pathogenesis of AM is still far from clear. Although the gut microbiome and metabolomics are thought to contribute to a variety of diseases, the role of them in AM has not been revealed. Objective To investigate changes in the gut microbiota and derived metabolites in AM mice. Method Female ICR mice were randomly assigned to AM and control groups, and pituitary transplantation was employed to perform AM modeling. Then, the fecal samples were obtained for microbial (16S rRNA gene sequencing) and metabolomic (liquid chromatography mass spectrometry, LC-MS) analysis. Result The results of gut microbiota analysis showed that the intestinal microbiota composition of AM mice was altered. The ratio of Firmicutes/Bacteroidetes and the relative abundance of Lactobacillus in AM group increased compared with the control group. Sixty differential expressed metabolites were identified in intestinal metabolites, mainly involved in steroid hormone biosynthesis, cysteine and methionine metabolism, and alanine, aspartate, and glutamate metabolism. Further, correlation analysis verified that L-methionine and L-cystine were negatively correlated with Bacteroides and positively correlated with Desulfovibrio. The Pregnenolone, Androsterone glucuronide, and Testosterone glucuronide were negatively correlated with Unidentified_Ruminococcaceae and Alistipes, whereas they positively correlated with Bacteroides. Conclusion AM mice have a unique gut microbiome and intestinal metabolites.